A high stress profile is associated with severe pain in oncology patients receiving chemotherapy. (June 2022) - Langford, Dale J.; Eaton, Linda; Kober, Kord M.; Paul, Steven M.; Cooper, Bruce A.; Hammer, Marilyn J.; Conley, Yvette P.; Wright, Fay; Dunn, Laura B.; Levine, Jon D.; Miaskowski, Christine
Abstract: Purpose: Oncology patients receiving chemotherapy can experience both cancer and non-cancer pain. In addition, oncology patients face numerous stressors and their responses are highly variable. Stress and pain are intricately linked. The purpose of this study was to evaluate for differences in pain characteristics and mood disturbance among oncology patients with distinct stress profiles. Methods: From a sample of 957 patients with and without pain, latent profile analysis identified three groups of patients with distinct stress profiles (i.e., Stressed, Normative, Resilient). In the subset of 671 patients with pain, receiving chemotherapy for breast, lung, gastrointestinal, or gynecologic cancer, we evaluated for differences among the stress profiles in terms of pain characteristics (e.g., intensity, qualities, interference) and mood disturbance (anxiety, depressive symptoms). Results: Compared to Normative patients (n = 333; 49.6%), Stressed patients (n = 305; 45.5%) reported higher levels of pain intensity, pain interference, anxiety, and depressive symptoms and more commonly described pain as throbbing, shooting, burning, exhausting, tiring, penetrating, nagging, miserable, and unbearable. Compared to Resilient patients (n = 33; 4.9%), Stressed patients reported significantly higher mood-related pain interference scores and more severe anxiety and depressive symptoms. Conclusions: A high stress profile is common (45.5%) and is associated with more severe pain and associated symptoms. Efforts to identify and target this group for interventions may improve patient outcomes. Highlights: Little is known about the associations between stress and pain characteristics. A high stress profile occurs in approximately 50% of oncology patients. A high stress profile is associated with severe pain and mood disturbance.